Gambaran Iklim Keselamatan pada Perawat dan Tenaga Penunjang Medis RSU Kota Tangerang Selatan - Melati Rizqiya Fitri; Siti Rahmah Hidayatullah Lubis (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2021)
Safety climate is employee’s perception about policy, program, and all the matters related to safety in the workplace that can affect worker’s safety behavior. Good safety behavior can create a safe working environment so as to be able to reduce workplace accidents. The results of preliminary study in General Hospital of Tangerang Selatan showed that most of the occupational injury were caused by unsafe behavior, and based on the assessment of perception of 20 workers showed that their perception about management’s commitment, management’s safety empowerment, management’s justice in safety, and risk priority were categorized as not good enough.This research is a descriptive research with cross sectional design. This research took place in November 2019 until February 2020. The samples were 176 workers from nurse stations and medical support installations. Sampling methods used was simple random sampling, and the instrument used was NOSACQ-50 questionnaire.Result shows that the dimension of worker safety priority and not-tolerated risk is categorized as not good enough and need improvement, with the final score 2.91. the others dimensios  of safety climate is categorized good.Therefore, management is advised to improve the sustainability of a systematic risk management program (HIRADC) and for workers, it would be better if the workers also participating in safety programme especially the program related to risk management in the hospital.Keywords: hospital, Nurse, NOSACQ50, Safety Climate